Mathematical Modeling of Fluids: Theory, Equations, and Applications - Dr Manju Bala (International Journal of Scientific Research in Science, Engineering and Technology, 2025)
This research paper explores the mathematical modeling of fluids, focusing on the fundamental principles, governing equations, and their applications in engineering, physics, and natural sciences. Fluid dynamics has a profound impact on various fields, including aerodynamics, oceanography, weather prediction, and biological systems. This paper delves into the key mathematical models used to describe fluid behavior, with particular emphasis on the Navier-Stokes and Euler equations, fluid flow classification, numerical methods, and practical applications. We examine advanced techniques in computational fluid dynamics (CFD), the challenges in solving complex fluid problems, and future research directions.